Anwa’al-Huruf Min Haitsu Amaliha WAAtsariha Dalam Perspektif Kontemporer - Ikhsandy Maulana; Anwar Sidik (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to examine the differences between classical (traditional) Arabic grammar and contemporary Arabic grammar in understanding Anwā‘ al-Hurūf min Ḥaythu ‘Amalihā wa Atharihā (types of particles in terms of their grammatical function and effect). To achieve this objective, the research compares the theoretical foundations, analytical approaches, and interpretations of particle functions presented in both grammatical traditions. This study employs a qualitative method with a descriptive-comparative approach through library research. Data were collected from classical Arabic grammar works written by early grammarians and contemporary grammar references influenced by modern linguistic theories. The collected data were analyzed by identifying, classifying, and comparing the concepts of ‘amal (grammatical function) and athar (grammatical effect) associated with various particles in Arabic sentence structures. The findings indicate that classical grammar emphasizes the stability of grammatical rules, the authority of linguistic tradition, and the preservation of established syntactic principles. In contrast, contemporary grammar adopts a more descriptive and functional perspective, focusing on language use, communicative context, and linguistic flexibility. These differences affect the interpretation of particle functions and their grammatical effects in sentence construction. The study concludes that both approaches possess complementary strengths. Therefore, integrating classical grammatical principles with contemporary linguistic insights can provide a more comprehensive understanding of Arabic grammar and contribute to more effective Arabic language learning in modern educational contexts.